1997
DOI: 10.1083/jcb.137.5.1185
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of α1(IV) Collagen Mutations in Caenorhabditis elegans and the Effects of α1 and α2(IV) Mutations on Type IV Collagen Distribution

Abstract: Type IV collagen is a major component of basement membranes. We have characterized 11 mutations in emb-9, the α1(IV) collagen gene of Caenorhabditis elegans, that result in a spectrum of phenotypes. Five are substitutions of glycines in the Gly-X-Y domain and cause semidominant, temperature-sensitive lethality at the twofold stage of embryogenesis. One is a glycine substitution that causes recessive, non–temperature-sensitive larval lethality. Three putative null alleles, two nonsense mutations and a deletion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 48 publications
(84 reference statements)
6
114
0
Order By: Relevance
“…In these animals, type IV collagen is reduced or absent from basement membranes, but is correspondingly seen to accumulate within the cells that synthesize it, possibly because of the high rate of ␣1(IV) to ␣2(IV) chain synthesis during development. 63 Using the immunofluorescence amplification technique and antibodies directed against the NC1 domain of the chain, we have been able to demonstrate for the first time the presence of the ␣3(IV) protein within human AS podocytes, a finding very special to AS patients, not seen in normal kidneys, and exceptional in other pathological conditions. The presence of both the transcripts and the protein indicate that the loss of the ␣3(IV) chain in Xlinked AS GBM results from events downstream of transcription, RNA processing, and protein synthesis.…”
Section: Discussionmentioning
confidence: 84%
“…In these animals, type IV collagen is reduced or absent from basement membranes, but is correspondingly seen to accumulate within the cells that synthesize it, possibly because of the high rate of ␣1(IV) to ␣2(IV) chain synthesis during development. 63 Using the immunofluorescence amplification technique and antibodies directed against the NC1 domain of the chain, we have been able to demonstrate for the first time the presence of the ␣3(IV) protein within human AS podocytes, a finding very special to AS patients, not seen in normal kidneys, and exceptional in other pathological conditions. The presence of both the transcripts and the protein indicate that the loss of the ␣3(IV) chain in Xlinked AS GBM results from events downstream of transcription, RNA processing, and protein synthesis.…”
Section: Discussionmentioning
confidence: 84%
“…Shifting to 25°C resulted in severe gonadal defects, which precluded the analysis of mig-17 suppression. To examine whether reduction of type IV collagen in the BM affects the suppression, we depleted a single copy of emb-9/␣1 chain of type IV collagen using the null allele emb-9(g23cg46) (13). We found that g23cg46/ϩ partially suppressed mig-17(k174) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Heterozygote truncating mutations have already been observed in collagen IV-related Alport syndrome, but null alleles for the C. elegans COL4A1 homologue, emb-9 and COL4A2 homologue let2 cause disruption of the basement membrane and embryonic lethality, although at a later stage than the G-Xaa-Yaa missense mutations. 28 The non-collagen domain of collagen IV alpha-2, but not alpha-1 chain, promotes cell adhesion, outgrowth of embryonic neurons and is responsible for strict regulation of the 2:1 stoichiometry of the triple helix. 18,[29][30][31] This could indicate that a disturbed ratio of procollagen alpha-1 and procollagen alpha-2 chains due to a heterozygous null allele of either COL4A1 or COL4A2 may lead to a disturbed or insufficient heterotrimer assembly and secretion.…”
Section: Pathogenesis Of Col4a2 Mutationsmentioning
confidence: 99%